Can AI Reduce Diagnostic Errors in Healthcare? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2018)
Diagnostic errors are a significant concern in the healthcare industry, posing substantial risks to patient safety and leading to suboptimal health outcomes....
Keywords: AI in Clinical Decision Support; Reduce; Diagnostic; Errors; Artificial Intelligence; Machine Learning; Healthcare